2016
DOI: 10.21707/gs.v10.n04a29
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of amino acids by leaching in feeds for shrimp

Abstract: Resumo -As rações para camarão estão entre as mais caras do setor de aquicultura principalmente porque esse tipo de ração deve ter alta estabilidade na água. Este trabalho teve, como objetivo, avaliar a estabilidade de aminoácidos em rações comerciais com diferentes teores proteicos, destinados a camarões na fase larval e juvenil, submetidas à lixiviação. As amostras de ração foram expostas ao processo lixiviatório durante período de tempo de 04, 08 e 12 horas. As análises de degradação de aminoácidos foram re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Fishmeal is known for its balanced amino acids, contributing to better growth (Wouters et al, 2001; Glencross et al, 2002; Gonzalez-Galaviz et al, 2020). However, the plant-based diets in this study showed higher rates of amino acid leaching (Prado et al, 2016), possibly affecting shrimp feed efficacy.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Fishmeal is known for its balanced amino acids, contributing to better growth (Wouters et al, 2001; Glencross et al, 2002; Gonzalez-Galaviz et al, 2020). However, the plant-based diets in this study showed higher rates of amino acid leaching (Prado et al, 2016), possibly affecting shrimp feed efficacy.…”
Section: Discussionmentioning
confidence: 73%
“…Fishmeal’s high- quality protein with balanced essential amino acids contributes to better growth and feed utilization in aquatic animals (Hua et al, 2019; Malcorps et al, 2019). Supplemented amino acids have also been studied for their ability to leach into the water, which can be a problem in shrimp feed due to their slow feeding behaviour (Prado et al, 2016). Despite being supplemented into the soya and pea–based diets, the levels of lysine, threonine and methionine were lower in Diets D1 (SE) and especially D2 (SS).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations